Видалення іонів Mn з водних розчинів фільтруючими матеріалами різного походження - Чернова, Наталія Миколаївна; Савченко, Ольга Олександрівна; Якупова, Ірина Володимирівна; Головач, Катерина Володимирівна (My University, 2018)
Запропоновано застосування природного та товарного фільтруючого матеріалів для вивчення процесу видалення іонів марганцю із водних розчинів. Наведено результати впливу дози сорбентів на основі природного матеріалу кальциту та каталітичного фільтруючого матеріалу Pyrolox на процес видалення іонів марганцю з модельних розчинів у статичних умовах. Досліджено ступінь видалення іонів Mn у кислому та лужному середовищах при різних дозах сорбентів. Встановлено, що у кислому середовищі сорбційна ємність зразків з різною дозою відрізняється незначно. Збільшення дози кальциту обумовлює зменшення залишкової концентрації іонів марганцю у розчині за рахунок підвищення рН середовища. Досліджено вплив лужного значення рН на ефективність видалення Mn кальцитом та Pyrolox. Ефективність видалення марганцю значно збільшилася порівняно із сорбцією у кислому середовищі. Природній матеріал кальцит сприяє ефективному видаленню марганцю з води за рахунок самостійного корегування значення рН до лужного середовища. Встановлено основні закономірності протікання процесів та визначено оптимальні умови очищення водних розчинів від іонів марганцю. Natural and commercial medium bed usage for studying manganese ions removal from aqueous solutions was proposed. Natural calcite material and catalytic medium bed Pyrolox doses influence results on manganese ions removal from simulated solutions under static conditions were given. Sorbent´s dose as a main factor determining purification efficiency was found. Calcite dose increase causes manganese ions residual concentration decrease due to pH medium contribution in water solution. Manganese ions concentration decreased only 11% after five days experiment in sample without calcite. It was established that one of important factors in effective process of manganese ions content reducing was pH value. In order to study main factors determining manganese ions removal efficiency process from model solution it was varying its pH range from acid to slightly alkaline by adding chloric acid and sodium bicarbonate. Mn ions removal degree in acidic and alkaline media at different sorbents doses was studied. It was established that sample´s sorption capacity with various doses in acidic medium differs insignificantly. The alkaline pH effect on Mn removal efficiency by calcite and Pyrolox was studied. The manganese removal effectiveness was increased significantly in comparison with sorption in acid medium. Model solution purification efficiency from manganese ions by calcite increased significantly at pH> 8.5. The natural calcite material contributes to effective manganese removal from water by self-adjusting pH value to alkaline medium. Purification efficiency of model solution in the acid and alkaline media by calcite and Pyrolox was calculated.The equilibrium ratio of manganese ions reducing concentration for accounting different sorbents initial concentrations in solution was introduced.The dependence of equilibrium ratio of reducing manganese ions concentration in solution and pH value from medium contact time was constructed.The main processes regularities were established and optimal conditions of aqueous solutions purification from manganese ions were determined.
Keywords: іони марганцю; кальцит; pyrolox; рН розчину; модельні розчини; manganese ions; calcite; pyrolox; simulated solutions; рН solution; кафедра технології цукру і підготовки води